Objective Assessment of Vergence after Treatment of Concussion-Related CI: A Pilot Study. Issue 1 (January 2017) - Scheiman, Mitchell M.; Talasan, Henry; Mitchell, G. Lynn; Alvarez, Tara L.
ABSTRACT: Purpose: To evaluate changes in objective measures of disparity vergence after office-based vision therapy (OBVT) for concussion-related convergence insufficiency (CI) and determine the feasibility of using this objective assessment as an outcome measure in a clinical trial. Methods: This was a prospective, observational trial. All participants were treated with weekly OBVT with home reinforcement. Participants included two adolescents and three young adults with concussion-related, symptomatic CI. The primary outcome measure was average peak velocity for 4° symmetrical convergence steps. Other objective outcome measures of disparity vergence included time to peak velocity, latency, accuracy, settling time, and main sequence. We also evaluated saccadic eye movements using the same outcome measures. Changes in clinical measures (near point of convergence, positive fusional vergence at near, Convergence Insufficiency Symptom Survey [CISS] score) were evaluated. Results: There were statistically significant and clinically meaningful changes in all clinical measures for convergence. Four of the five subjects met clinical success criteria. For the objective measures, we found a statistically significant increase in peak velocity, response accuracy to 4° symmetrical convergence and divergence step stimuli, and the main sequence ratio for convergence step stimuli. Objective saccadic eye movements (5 and 10°) appeared normal pre-OBVT and did not show any significant change after treatment. Conclusions: This is the first report of the use of objective measures of disparity vergence as outcome measures for concussion-related convergence insufficiency. These measures provide additional information that is not accessible with clinical tests about underlying physiological mechanisms leading to changes in clinical findings and symptoms. The study results also demonstrate that patients with concussion can tolerate the visual demands (over 200 vergence and versional eye movements) during the 25-minute testing time and suggest that these measures could be used in a large-scale randomized clinical trial of concussion-related CI as outcome measures.